On the Practical Output Feedback Stabilization for Nonlinear Uncertain Systems - Benabdallah, A. (Nonlinear Analysis: Modelling and Control, 2009)
In this paper, we treat the problem of output feedback stabilization of nonlinear uncertain systems. We propose an output feedback controller that guarantees global uniform practical stability of the closed loop system.